2015
DOI: 10.2135/cropsci2014.04.0295
|View full text |Cite
|
Sign up to set email alerts
|

Selfing Rate in an Alfalfa Seed Production Field Pollinated with Leafcutter Bees

Abstract: A utotetraploid alfalfa (2n = 4x = 32) is the third largest crop by acreage in the United States with an estimated 28 million kg of seed produced per year (NASS, 2009). Although alfalfa tends to outcross (i.e., xenogamous), it is a self-compatible species meaning that self-pollination or "selfing" is possible. Selfing in alfalfa is more likely to occur in the absence of pollen from another genotype, suggesting that, when present, outcross pollen may outcompete self pollen (Viands et al., 1988). Selfing has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…The uneven pollen‐parent fecundity distribution in our trial corresponds to Riday, Reisen, Raasch, Santa‐Martinez, and Brunet () and Riday () who found that pollen‐parent fecundity distributions are uneven in polycrosses with most forage Legumes. The distribution in the present study could be somewhat biased due to the lower success rate of assigning parentage thus making certain pollen‐parents more likely to be identified based on rare SSR alleles.…”
Section: Discussionsupporting
confidence: 84%
“…The uneven pollen‐parent fecundity distribution in our trial corresponds to Riday, Reisen, Raasch, Santa‐Martinez, and Brunet () and Riday () who found that pollen‐parent fecundity distributions are uneven in polycrosses with most forage Legumes. The distribution in the present study could be somewhat biased due to the lower success rate of assigning parentage thus making certain pollen‐parents more likely to be identified based on rare SSR alleles.…”
Section: Discussionsupporting
confidence: 84%
“…The other strategy is to minimize inbreeding by selecting enough parents to make "broad"based synthetics (Busbice, 1969;Hill et al, 1988). Regardless if a narrow-or broad-based synthetic mating strategy is used, with associated inbreeding due to mating among relatives in both cases, a proportion of seed is expected to result from selfing (Riday et al, 2015). On the other hand, a significant number of breeders continue to use only a few parents to create so-called "narrow"based synthetics, despite theoretical work showing that this strategy should lead to inbreeding depression (Busbice, 1969).…”
Section: Measuring the Inefficiency Of Allowing Self-pollinated Alfalmentioning
confidence: 99%
“…The 63 plants were completely randomized prior to each pollination. Self-pollination occurs at low frequencies in bee-pollinated alfalfa (Riday et al 2015). Therefore, polycross size (N) was determined based on paternal parents detected during paternity testing of progeny and seed-parents which produced seed c Dimensions include immediate size of polycross; actual indoor room size was larger Table 1).…”
Section: Polycrossesmentioning
confidence: 99%
“…The parents and majority of progeny of C584Y, WI21, and C276 were extracted as described in Riday (2011); additional progeny DNA samples analyzed since the 2011 paper were extracted using methodologies described in Riday et al (2013). Finally, parent DNA from the KU09B polycross was extracted as described in Riday et al (2013), while progeny DNA extracted directly from seed was accomplished as described in Riday et al (2015).…”
Section: Dna Extraction Pcr Pcr Product Evaluation and Paternity Tmentioning
confidence: 99%
See 1 more Smart Citation